Age and disability drive cognitive impairment in multiple sclerosis across disease subtypes. (August 2017) - Ruano, Luis; Portaccio, Emilio; Goretti, Benedetta; Niccolai, Claudia; Severo, Milton; Patti, Francesco; Cilia, Sabina; Gallo, Paolo; Grossi, Paola; Ghezzi, Angelo; Roscio, Marco; Mattioli, Flavia; et al.
Background: There is limited and inconsistent information on the clinical determinants of cognitive impairment (CI) in multiple sclerosis (MS). Objective: The aim of this study was to compare the prevalence and profile of CI across MS disease subtypes and assess its clinical determinants. Methods: Cognitive performance was assessed through the Brief Repeatable Battery and the Stroop test in consecutive patients with MS referred to six Italian centers. CI was defined as impairment in ⩾ 2 cognitive domains. Results: A total of 1040 patients were included, 167 with clinically isolated syndrome (CIS), 759 with relapsing remitting (RR), 74 with secondary progressive (SP), and 40 with primary progressive (PP) disease course. The overall prevalence of CI was 46.3%; 34.5% in CIS, 44.5% in RR, 79.4% in SP, and 91.3% in PP. The severity of impairment and the number of involved domains were significantly higher in SP and primary progressive multiple sclerosis (PPMS) than in CIS and RR. In multivariable logistic regression analysis, the presence of CI was significantly associated with higher Expanded Disability Status Scale (EDSS) and older age. Conclusion: CI is present in all MS subtypes since the clinical onset and its frequency is increased in the progressive forms, but these differences seem to be more associated with patient age and physical disability than to disease subtype per se.